Эффективность дополнительного ускорения движущихся массивных объектов электромеханическим индукционным преобразователем - Болюх, Владимир Федорович; Корытченко, Константин Владимирович; Кочерга, Анатолий Григорьевич (НТУ "ХПИ", 2011)
The electromechanical induction converter for additional acceleration of moving massive objects is offered to use. The method for selection parameters of the highly effective converter, based on determination of minimum of objective function in search space combined with using global and local optimization methods is developed. For global optimization genetic algorithms are used, and as a method of local optimization Nidler-Mid’s method which is carrying out deformation of the current simplex is used. The general laws of the most effective variants of converters are established and it is shown, that their efficiency is much higher, than at known converters.
Keywords: электромеханический преобразователь; индукционный преобразователь; ускорение; электропроводящий якорь; ускоряющий импульс; массивный объект